THE EFFECT OF COMBINED EXERCISES ON MOVEMENT SPEED, PHYSIOLOGICAL MARKERS, AND BASIC SKILLS OF FOOTBALL GOALKEEPERS - Mustafa Mohammed Shanan (Proximus Journal Publishing, 2025)
The purpose of the current study was to examine the effects of combined exercise training on movement speed, gender-specific biochemical responses, and on the fundamental movement skills of male football goalkeepers. The study was conducted with a sample of 12 primary schools, using a quasi-experimental design: non-equivalent groups of equivalent proportion. The study sample was (n=12) First-division goalkeepers who played for clubs in Al-Diwaniyah Governorate during the 2023–2024 season, divided equally between both the groups. Experimental group followed combined exercises training-based programme, and control group followed a traditional training programme. Exclusive and save statistical equivalence following pre-tests. The 12-week interventions course consisted of 36 sessions in total, with three sessions each week. The follow-up results proved that the experimental group’s post-test score in all the selected variables was significantly better. These results highlight the effect of joint training programs on increasing the physiological responsiveness, the speed of movement as well as the core goalkeeping skills.
Keywords: physiological responsiveness; movement; combined